1985
DOI: 10.1007/bf00383318
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrofolate reductase activity and resistance to aminopterin in various species of Drosophila

Abstract: The aim of our work was to compare the mechanisms of resistance to aminopterin, inhibitor of the dihydrofolate reductase enzyme, between different Drosophila species and those described for cultured cells. Moreover we compared the systematic species divisions based on morphological traits and those based on a molecular approach. For this purpose, the effect of aminopterin on viability and wing phenotype was studied in different Drosophila species. Dihydrofolate reductase was measured in adult flies. We found a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Aminopterin, an analog of methotrexate, induces massive cell death and a well characterized wing phenotype when cell death occurs in the part of the wing disc that will give the future wing margin. 28 This drug is an inhibitor of dihydrofolate reductase activity, and therefore inhibits DNA replication and the G1/S transition.…”
Section: Ectopic Expression Of Human Twist Inhibits P53-dependent Apomentioning
confidence: 99%
“…Aminopterin, an analog of methotrexate, induces massive cell death and a well characterized wing phenotype when cell death occurs in the part of the wing disc that will give the future wing margin. 28 This drug is an inhibitor of dihydrofolate reductase activity, and therefore inhibits DNA replication and the G1/S transition.…”
Section: Ectopic Expression Of Human Twist Inhibits P53-dependent Apomentioning
confidence: 99%
“…Re-replication attempts and subsequent chromosome breaks in the vicinity of replication origins then ultimately result in DNA amplification (Singer et al 2000). Thus, it is curious that, in Drosophila, acquired resistance has only been reported to occur by substitution mutations resulting in a DHFR with an altered affinity to MTX (Silber et al 1985;Neumann et al 2003;Affleck et al 2006). To determine if the observed disparity between Drosophila and murine cells could be attributed to differences in cell growth characteristics, the effect of MTX on cell proliferation was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of a closed inter-relation between the eight parameters tested made the interpretation of our results rather difficult. We had previously studied the nucleotide metabolism variability in different species (Silber et a!., 1985) and in different wild-type strains of D. melanogaster (Le Menn et at., 1987a and b). These results indicated that with the exception of the vg mutant, aminopterin resistance is not correlated with DHRF activity but mainly with the use of salvage pathways and particularly TdR.…”
Section: Discussionmentioning
confidence: 99%